2014
DOI: 10.1155/2014/409739
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Ethanol-Diesel Blends on Performance and Exhaust Emissions of Diesel Engines

Abstract: Ethanol is a promising alternative fuel, due to its renewable biobased origin. Also, it has lower carbon content than diesel fuel and it is oxygenated. For this reason, ethanol is providing remarkable potential to reduce particulate emulsions in compression-ignition engines. In this study, performance of ethanol-diesel blends has been investigated experimentally. Tested fuels were mineral diesel fuel (E0D100), 15% (v/v) ethanol/diesel fuel blend (E15D85), and 30% (v/v) ethanol/diesel fuel blend (E30D70). First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…According to Rakopoulos DC [37], the nitrogen oxides emissions reduced for diesel-ethanol emulsified fuel and gradually decreases with increasing percentage of ethanol in the fuel blend. Combustion temperature and oxygen content inside engine cylinder are two major reason for NOx formation [53]. This decrement of NOX emissions occurs because of temperature reducing effect of ethanol due to its lower calorific value and it is gradually decreasing with ethanol concentration.…”
Section: Nox Emissionsmentioning
confidence: 99%
“…According to Rakopoulos DC [37], the nitrogen oxides emissions reduced for diesel-ethanol emulsified fuel and gradually decreases with increasing percentage of ethanol in the fuel blend. Combustion temperature and oxygen content inside engine cylinder are two major reason for NOx formation [53]. This decrement of NOX emissions occurs because of temperature reducing effect of ethanol due to its lower calorific value and it is gradually decreasing with ethanol concentration.…”
Section: Nox Emissionsmentioning
confidence: 99%
“…They discovered that there was a 51% reduction in smoke emission with the fumigation method, and a 32% reduction in smoke emission with the emulsion method. Sandalci et al [27] investigated the effects of different proportions of ethanol-diesel blends with emulsions on performance and emissions. They reported that as the ethanol ratio in the blend increased, the smoke emission decreased, but the CO emissions increased.…”
Section: Introductionmentioning
confidence: 99%
“…The ethanol use on compression ignition engines by direct injection into the combustion chamber, by blends method, is limited due to low density, low viscosity, and because the cetane number is insufficient [15]. Without modifying the engine structure, the limit of 15% ethanol mixed with diesel oil is indicated, in a volumetric ratio (v/v) [25]. For using ethanol in diesel engines, typically, it applies the fumigation method [26].…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al [15] and Sandalci et al [25] cite that among the methods used for ethanol use on diesel engine, fumigation is the more studied, for enabling the higher diesel substitution rate by ethanol, in energy terms (up to 50%), and for requiring fewer changes on the engine physical structure. Besides the use of commercial ethanol, with low water concentration, in recent years, studies have been carried out aiming to characterize the use of ethanol with high water concentrations (wet ethanol) on spark ignition engine [27][28][29][30] and compression ignition engines.…”
Section: Introductionmentioning
confidence: 99%